Diverse plant-associated pleosporalean fungi from saline areas: ecological tolerance and nitrogen-status dependent effects on plant growth - Qin, Yuan; Pan, Xueyu; Kubicek, Christian; Druzhinina, Irina; Chenthamara, Komal; Labbé, Jessy L.; Yuan, Zhilin (Frontiers in Microbiology, 2017)
Similar to mycorrhizal mutualists, the rhizospheric and endophytic fungi are also considered to act as active regulators of host fitness (e.g., nutrition and stress tolerance). Despite considerable work in selected model systems, it is generally poorly understood how plant-associated fungi are structured in habitats with extreme conditions and to what extent they contribute to improved plant performance. Here, we investigate the community composition of root and seed-associated fungi from six halophytes growing in saline areas of China, and found that the pleosporalean taxa (Ascomycota) were most frequently isolated across samples. A total of twenty-seven representative isolates were selected for construction of the phylogeny based on the multi-locus data (partial 18S rDNA, 28S rDNA, and transcription elongation factor 1-α), which classified them into seven families, one clade potentially representing a novel lineage. Fungal isolates were subjected to growth response assays by imposing temperature, pH, ionic and osmotic conditions. The fungi had a wide pH tolerance, while most isolates showed a variable degree of sensitivity to increasing concentration of either salt or sorbitol. Subsequent plant–fungal co-culture assays indicated that most isolates had only neutral or even adverse effects on plant growth in the presence of inorganic nitrogen. Interestingly, when provided with organic nitrogen sources the majority of the isolates enhanced plant growth especially aboveground biomass. Most of the fungi preferred organic nitrogen over its inorganic counterpart, suggesting that these fungi can readily mineralize organic nitrogen into inorganic nitrogen. Microscopy revealed that several isolates can successfully colonize roots and form melanized hyphae and/or microsclerotia-like structures within cortical cells suggesting a phylogenetic assignment as dark septate endophytes. This work provides a better understanding of the symbiotic relationship between plants and pleosporalean fungi, and initial evidence for the use of this fungal group in benefiting plant production.